Peranan Fear of Missing Out dan Attention-Seeking Behavior terhadap Problematic Social Media Use pada Remaja Pengguna Instagram - Syihab, Aisyah; Rani, Dyah (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2023)
Problematic social media use (PSMU) is one of the problems faced by adolescents. One of the social media that is often used by them is Instagram. There are many things that affect PSMU, including fear of missing out (FoMO) and attention-seeking behavior, but it is not yet known which one is more responsible for making individuals experience PSMU. Therefore, this study aims to analyze the role of FoMO and attention-seeking behavior on PSMU in adolescents who use Instagram. Participants in this study amounted to 167 adolescents aged 13-18 years old, with a non-probability web survey-based sampling method (self-selected polls). The results of this study are FoMO and attention-seeking behavior simultaneously have a positive role on PSMU in adolescent who are Instagram users by 32.4% and a significance value of .000 (p < .05) which was tested using analytical techniques: Multiple Linear Regression. Meanwhile, if tested individually, attention-seeking behavior has no role in PSMU. Suggestions for further researcher is to conduct research with the same variables on social media users or at different stages of development, to see if the same thing happens to other social media, or at other stages of development.